Digital servitization strategies for SME internationalization : the interplay between digital service maturity and ecosystem involvement - Kolagar, Milad; Reim, Wiebke; Parida, Vinit; Sjödin, David (Emerald, 2022)
Purpose The purpose of this study is to understand how digital servitization enables the process of internationalization for industrial SMEs. Design/methodology/approach The present study has adopted an exploratory multiple case study, conducting a total of 40 interviews in a two-phased approach to data collection. The first phase consisted of exploratory interviews with twenty-six industrial SMEs connected to the manufacturing industry in Sweden and Finland. Then, six SMEs were selected in the second phase to participate in additional in-depth interviews. Findings First, this study identifies three gradual enabling phases concerned with the digital service maturity of SMEs consisting of digital awareness, digital service innovation and digital service mass customization. Second, the three interdependent phases of ecosystem knowledge synergy, ecosystem integration and ecosystem value co-creation were identified to improve ecosystem involvement. Finally, a process framework has been developed for SME internationalization consisting of a digital servitization innovation strategy, a digital servitization ecosystem strategy and a digital servitization scaling strategy. Originality/value The present research contributes to how digital servitization enables SME internationalization by demonstrating how the development of digital service offerings and ecosystem partnerships supports the internationalization process. This research extends the literature by proposing a process framework for the digital-servitization-enabled internationalization of SMEs. This process perspective provides a richer explanation of the complex interplay between servitization, digitalization and ecosystems choices, which supports the expansion into international markets.
Keywords: Internationalization; SMEs; Digital servitization; Digital service maturity; Business ecosystem; Ecosystem involvement; small and medium-sized enterprises; fi=Strateginen johtaminen|en=Strategic Management|